2011
DOI: 10.1108/02630801111118403
|View full text |Cite
|
Sign up to set email alerts
|

The flexural strength of earth‐block masonry for sustainable walling

Abstract: PurposeThe purpose of the paper is to explore the structural feasibility of substituting traditional thick joint mortars with earth slurry mortars modified with varying amounts of sand. Thin jointing of earth blocks would reduce the cost of sustainable earth construction.Design/methodology/approachCompressive strength of earth‐block cubes was determined. Flexural strength was measured using the BRE electronic bond wrench, which enables block couplets to be tested quickly and accurately. Three samples of earth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…It is noted in Table2that the silt and clay contents of the soil used in this study (tested by Ra et al[33]) are generally higher compared to those reported by other researchers. The silt and clay contents for the soil tested by Williams et al[53] from the Appley region in England compared closely with this soil.…”
supporting
confidence: 55%
“…It is noted in Table2that the silt and clay contents of the soil used in this study (tested by Ra et al[33]) are generally higher compared to those reported by other researchers. The silt and clay contents for the soil tested by Williams et al[53] from the Appley region in England compared closely with this soil.…”
supporting
confidence: 55%